Genomic analysis reveals G3P[13] porcine rotavirus A interspecific transmission to human from pigs in a swine farm with diarrhoea outbreak. (9th February 2021) - Yan, Nan; Yue, Hua; Wang, Yuanwei; Zhang, Bin; Tang, Cheng
Abstract : Rotavirus A (RVA) is a major diarrhoea-causing pathogen in young animals and children. The zoonotic potential of RVA has received extensive attention in recent years. In May 2018, an outbreak of diarrhoea among piglets occurred on a swine farm in Sichuan province, PR China. RVA was detected in 95.7 % (22/23) of piglet samples, 60 % (9/15) of sow samples and 100 % (3/3) of pig-breeder faecal samples. The predominant RVA genotype on this swine farm was G3P[13], and G3P[13] RVA was also detected in the three breeder faecal samples. Three G3P[13] RVA strains were isolated from a piglet faecal sample, a sow faecal sample and a pig-breeder faecal sample, and were named SCLS-X1, SCLS-3 and SCLS-R3, respectively. The complete sequences of 11 gene segments of these three isolates were derived. Phylogenetic analysis showed that ten gene segments (VP7, VP4, VP1–VP3 and NSP1–NSP5) of pig-breeder isolate SCLS-R3 were closely related to pig isolates SCLS-X1 and SCLS-3 from this farm. Only the VP6 gene shared higher homology with human RVA strain I321. Therefore, a G3P[13] porcine RVA strain most likely infected pig breeders. These results provided the first complete epidemiological link demonstrating interspecies transmission of G3P[13] RVA from pigs to human. Our data contribute to an improved understanding of the genetic evolution and interspecies transmission of RVA.